2016
DOI: 10.1097/iae.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Significance of Cystic Changes After Epiretinal Membrane Surgery With Internal Limiting Membrane Removal

Abstract: Purpose To assess the prevalence and significance of cystic changes after internal limiting membrane (ILM) peeling during epiretinal membrane (ERM) surgery. Methods A retrospective review was performed on 64 patients who underwent pars plana vitrectomy (PPV) with membranectomy for idiopathic ERM between January 2010 and January 2012 by a single physician. PPV alone (Group 1, n=32) or in combination with phacoemulsification (Group 2, n=32) were performed. Peeling of the ERM was assisted by triamcinolone, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 9 publications
0
19
0
2
Order By: Relevance
“…The incidence rate of postoperative IRF including persistent preoperative IRF was 29.1% at 6 months, and the incidence rate of new IRF was 41% (49 out of 119) in the eyes without preoperative IRF. Previous studies have reported widely varying postoperative IRF incidence rates, 13 to 64% [5][6][7], and new IRF incidence rates, 1 to 15.6% [5,7,8]. It is likely that the highest incidence rate [6] would represent thickening of the macula by both mechanical deformation and presence of fluid, as postoperative macular edema was assessed based on macular thickness measured by OCT and not based on the presence of IRF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence rate of postoperative IRF including persistent preoperative IRF was 29.1% at 6 months, and the incidence rate of new IRF was 41% (49 out of 119) in the eyes without preoperative IRF. Previous studies have reported widely varying postoperative IRF incidence rates, 13 to 64% [5][6][7], and new IRF incidence rates, 1 to 15.6% [5,7,8]. It is likely that the highest incidence rate [6] would represent thickening of the macula by both mechanical deformation and presence of fluid, as postoperative macular edema was assessed based on macular thickness measured by OCT and not based on the presence of IRF.…”
Section: Discussionmentioning
confidence: 99%
“…Frisina et al [5] reported an incidence rate of about 10% for postoperative CME and new CME, as assessed by six radial scans (not a volume scan). Dolz-Marco et al [7] compared the incidence rates of new IRF depending on whether combined phacoemulsification was performed or not, using macular cube scans, and reported the incidence to be 6.3% in the vitrectomy only group and 25% in the combined surgery group. In the current study, when patients were similarly divided into two subgroups, similar incidence rates, i.e., 6.9% among patients who underwent vitrectomy alone and 37.3% among those who underwent combined surgery, were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated an association between the external limiting membrane, and ellipsoid zone with the post-operative visual acuity outcomes and metamorphosia. 12-13 Post operative complications of ERM removal such as swelling of the arcuate nerve fiber layer, cystoid macular edema, delayed new-onset inner nuclear layer cystic changes, and extrafoveal macular holes after ERM surgery have been reported and can now be followed by OCT. 14, 15,16 …”
Section: Introductionmentioning
confidence: 99%